Iestādes faktiskā rīcība administratīvajā procesā - Auziņa, Arita (Latvijas Universitāte, 2007)
Darbs veltīts faktiskās rīcības jēdziena analīzei. Autore darbā aplūko faktiskās rīcības jēdziena vēsturisko attīstību, analizējot tiesu praksi pirms APL pieņemšanas un pēc tās. Atsevišķi aplūkotas atsevišķās APL faktiskās rīcības pazīmes, to izpratne administratīvo tiesu nolēmumos. Uzmanība veltīta arī pieteikuma par faktisko rīcību sastādīšanai, ārpustiesas izskatīšanas kārtībai un tiesas kompetences robežām, izskatot pietikumu par iestādes faktisko rīcību.

The Article is devoted to the analysis of actual action of institution in administrative procedure. The author grounds the inquiry basically upon the evaluation of legal framework which is set for the actual action of institution as well as the assessment of administrative court practice. The author starts the exploration with the understanding of notion of actual action of institution in administrative procedure. As the Administrative Procedure Law came into force only in the Year 2004 the practice of courts of general jurisdiction is analysed. It is concluded that the understanding of the notion was quite vague at that time although it has to be admitted that it wasn’t completely unknown. After that the Article examines the notion of actual action of institution in Administrative Procedure Law as well as in administrative court practice. The formulation of the notion in the law has passed through slight changes and can be described as stable. The same can be said about the court practice. The author finds altogether six independent features the notion consists of although in legal literature as well as in court practice different number of features is sometimes distinguished. When the features of the notion are distinguished the Article turns to the analysis of each particular feature by using the interpretation given in administrative courts decisions. As most of the features of the notion of actual action of institution are similar to the features of the notion of administrative act special attention is paid to dissimilar features namely that contrary to administrative act actual action has factual not legal consequences. Also the particularities regarding the similar features are analysed. In the final part of the Article the author discusses the procedural requirements regarding actual action of institution. Before the application at court the preliminary proceedings has to be passed. The competence of the court in deciding the case where actual action of the institution is contested has to be understood. In the end the court application has to be drafted in a proper manner.
Actual Action of Institution in Administrative Procedure
Keywords: Tiesības